MAX inactivation is an early event in GIST development that regulates p16 and cell proliferation - Inga-Marie Schaefer (Nature Portfolio, 2017)
In gastrointestinal stromal tumours early mutations in known genes are frequently followed by chromosome 14q deletion. Here the authors find mutations resulting in loss of MAX protein expression conserved between primary tumours and metastases in the same patients, suggesting thatMAXmutation is an early event.